DIRECTIVES AS A TOOL FOR CORPORATE MANAGEMENT - A. Yakovlev (Вестник университета)
This article is devoted to the issues of directive voting of a member of the board of directors (supervisory board) as a representative of the owner (shareholder) in econom-ic societies. This instrument of corporate governance is most widespread in companies with state participation (in particular, whose shareholder is the Russian Federation). The use of di-rectives is ambiguous. Among the main arguments for its application is the reduction of risks of the adoption by members of the collegial body a decision that runs counter to the interests of the shareholder (participant) of the company.